A rare case of vaginal vault prolapses after vaginal hysterectomy in North India: managed via sacrocolpopexy - Kataria, Ritu; Tanya; Kumar, Rajneesh; Bains, Sunil S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Vaginal vault prolapse refers to the descent of the upper portion of the vagina (apex or dome) into the vaginal canal or beyond the vaginal introitus, typically following a hysterectomy. This condition is a rare but significant long-term complication, with an incidence ranging from 0.1% to 18.2% after vaginal or abdominal hysterectomy. It may present in isolation or in conjunction with other pelvic organ prolapse disorders, such as cystocele, rectocele, or enterocele. Risk factors include advancing age, multiparity, chronic increased intra-abdominal pressure, and poor pelvic support following surgery. Sacral colpopexy especially via the abdominal approach remains the gold-standard surgical treatment due to its superior anatomical and functional outcomes and lower recurrence rates when compared to vaginal repairs. The procedure involves attachment of the vaginal apex to the sacral promontory using a synthetic mesh, restoring normal vaginal axis and support. Despite its clinical relevance, vaginal vault prolapse with a large enterocele remains underreported in certain regions, particularly in North India. A lack of awareness and underdiagnosis often delay appropriate management, especially in rural populations. We present a case of a 63-year-old woman with a history of vaginal hysterectomy 13 years prior, who presented to our tertiary care center with a symptomatic vaginal vault prolapse associated with a large enterocele. She was successfully managed by open abdominal sacral colpopexy and discharged in stable condition.